Astaxanthin Ameliorates the Lipopolysaccharides-Induced Subfertility in Mouse via Nrf2/HO-1 Antioxidant Pathway - Lei Wang; Lili Zhuang (SAGE Publishing, 2019)
The endotoxin lipopolysaccharide (LPS) exists in human semen, which is associated with reduced sperm quality. Studying the LPS-impaired spermatozoa motility and viability, and discovering effective therapeutic treatments have crucial importance. The time-course and dose-response experiments were performed to optimize the treatment dose and time of astaxanthin and LPS on mouse spermatozoa motility and viability. Sperm kinetics and morphology, reactive oxygen species production, in vitro fertilization, and developmental competence were examined to evaluate the protective effects of astaxanthin on spermatozoa after LPS exposure. The activity of nuclear factor erythroid 2-related factor-2/heme oxygenase 1 (Nrf2/HO-1) pathway was detected by quantitative reverse transcription polymerase chain reaction and Western blot. Astaxanthin improves LPS-impaired spermatozoa motility, viability, morphology, and activity; reduces LPS-induced spermatozoa oxidative stress; and alleviates LPS-impaired fertilization and embryo development through activating Nrf2/HO-1 antioxidant signaling pathway. Astaxanthin might be a potential treatment for LPS-induced subfertility.